Page - Pierce, Tamora (New York : Random House, 2000)
Keladry of Mindelan continues her training to become a squire with the aid of a new maid, the support of her friends, interference from some other pages, and some serious, even dangerous opposition.
Sequel to: First test.
Sequel: Squire.
Keywords: Knights and knighthood -- Fiction; Sex role -- Fiction; Fantasy